Factors influencing sleep disorders in perimenopausal women: a systematic review and meta-analysis - Zeng, Weisi; Xu, Jialan; Yang, Ying; Lv, Meiling; Chu, Xin (Frontiers in Neurology, 2025)
BackgroundTo determine the influencing factors of sleep disorders in perimenopausal women by Meta-analysis.MethodsA comprehensive literature search was conducted by PubMed, Embase, CINAHL, and Web of Science(from inception to December 1,2023). Two researchers independently performed literature screening, quality evaluation and data extraction, and Stata16.0 software were used for Meta-analysis.ResultsA total of 12 studies involving 11,928 perimenopausal women with sleep disorders were included. The results of Meta-analysis showed that depression(OR = 2.73, 95%CI 1.65 ~ 4.52), hot flashes (OR = 2.70, 95%CI 1.81 ~ 4.02), chronic disease (OR = 1.39, 95%CI 1.24 ~ 1.56) and psychotropic drug use(OR = 3.19, 95%CI 1.31 ~ 7.77) were risk factors for sleep disorders in perimenopausal women (p < 0.05).ConclusionSleep disorder is one of the most common symptoms in perimenopausal women, and its influencing factors should be paid attention to. Healthcare managers can further improve and standardize the prevention and management of sleep disorders in perimenopausal women according to the influencing factors, accurately identify high-risk groups, implement intervention measures, and reduce the severity and incidence of sleep disorders in perimenopausal women.